Separation of trivalent chromium complexes by ion exchange chromatography using cation exchanger - 411919 Hamdya Sabrina Mohidin Yahya; Mohd Nordin Garif (supervisor) (Skudai : Universiti Teknologi Malaysia, 2008)
Project Paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2008